Impact of foreign exchange reserves to foreign exchange dinar/dollar in Algeria analytical econometric study since 1990-2019 - Bouchemal, Mohammed; Homida, Mokhtar (Dirassat Journal Economic Issue, 2020)
The objective of this study is to learn about the development of foreign exchange reserves in Algeria and to show the effect of foreign currency reserves on the exchange rate of the dinar / dollar in Algeria during the period 1990-2019, To study and describe the relationship between the variables of the study, the analysis was applied using the basic compounds (APC), To achieve this goal, the stability of the time series was examined through the application of the Dicky Fuller test. The Johannes method was used to test a long-term stable relationship, And through the tests the results showed the existence of the integration of the joint between these two variables, that is, there is a single long-term relationship between the reserve cash and the exchange rate in Algeria.